Economic Development and Demographic Changes in the economy of Himachal Pradesh from 1980-81 to 2010-11 - Latta, Amar; Sharma, Sunesh Kumar (British Journal of Healthcare and Medical Research, 2019)
Development has been appropriately conceptualized as a process, which improves the quality of life of people. Economic planning has been used in the country as an instrument for bringing about uniform regional development because one of the main objectives of the developmental programmes has been a progressive reduction in regional disparities in the pace of development. The main objective of the paper is to study the Economic development and demographic changes in the economy of Himachal Pradesh. PCA and Coefficient of Variance methods has been used in the study. To classify the districts according to the category of economic development and demographic changes from 1980-81 to 2010-11 in the Economy of Himachal Pradesh. This paper is based on secondary data. The required data have been collected entirely from secondary sources. The analysis of economic development and demographic changes shows that Lahaul & Spiti and Kinnaur were very highly developed in the level of economic development and in the demographic changes. Three districts namely Lahaul & Spiti, Chamba and Hamirpur were very highly developed. In the economic development three districts namely Bilaspur, Solan, Hamirpur were situated in the category of highly developed and only one district Kinnaur positioned in the level of demographic changes. In 2010-11 two districts Lahaul & Spiti and Solan were very highly developed in economic developed and three districts Kinnaur, Lahaul & Spiti and Chamba were very high developed in the demographic changes. In the highly developed category four districts namely Kinnaur, Bilaspur, Hamirpur and Chamba were highly developed in economic development, whereas, three districts namely Hamirpur, Bilaspur, and Kullu were in the same category in the demographic changes.